DEVELOPMENT OF A DEVICE FOR COOLING LADLE LINERS FOR CASTING LADLES - Aripova, Nazgul; Nikiforov, Alexander; Kulagin, Vladimir; Prikhodko, Evgeniy; Kinzhibekova, Akmaral; Karmanov, Amangeldy; Plevako, Anzhela (Journal of Applied Engineering Science, 2026)
This article focuses on the controlled cooling process of the linings of ferroalloy production ladles. Analysis of the operating conditions of the linings revealed that temperature stresses during heating and cooling are the main cause of damage to the linings of high-temperature units. At the enterprise in question, the cooling process is uncontrolled when the lining is exposed to the workshop atmosphere. This leads to cracks forming in the lining and its subsequent destruction. Cooling schedules have been developed for the ladles under consideration, during which the resulting thermal stresses do not damage the lining. A device has been developed for the ladle liners to ensure the cooling process is kept on schedule. Incomplete liner replacement involves cooling the ladle by supplying a mixture of combustion gases from the ladle heating booth and air. The liner is cooled using a mixture of three media: ambient air from the workshop, combustion products from the ladle heating stand, and combustion products from the ferroalloy gas burnt in the burner. A cooling schedule for casting ladle liners has been developed to ensure that thermal stresses do not exceed the strength limit of the refractory materials. At the same time, the cooling time is reduced from 19 hours 30 minutes to 6 hours 50 minutes. The developed device enables the outer and inner walls of the lining to be cooled, secondary resources (ferroalloy gas and combustion products from the ladle heating stand) to be used.
Keywords: lining cooling, refractories, temperature stresses, tensile strength, temperature regime